Approach to Phraseographical Representation of the Lemma of Locutions - Boughaba, Mohammed (Universidad Pedagógica y Tecnológica de Colombia, 2019)
etting of locutions ́ lemma raises a number of pitfalls. These pitfalls become more acute, because the lemma, in this case, does not correspond to a simple lexeme, but a multiverbal unit. In fact, it is often difficult to decide under which component of those that make up the locution should be lemmated, which explains why dictionaries do not agree when determining the lemma of this type of phraseological units. This contribu- tion tries to show how the lemma of locutions is described in several general monolingual and phraseological dictionaries. To do this, we will clarify several issues related to this topic, such as the canonical form, the contour elements, the insertion of some elements in the lemma, the prepositional regime, etc